2009
DOI: 10.1021/om900694u
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of [o-(Fluorodimethylsilyl)phenyl]lithium with GeCl2 and SnCl2: Preparation of Polyfunctionalized Four-Membered and Five-Membered Cyclic Linkages of Heavier Group 14 Elements

Abstract: Reactions of [o-(fluorodimethylsilyl)phenyl]lithium (1) with GeCl 2 and SnCl 2 produce benzosilagermacyclobutene 2 and benzosiladistannacyclopentene 3, respectively, both of which have o-(fluorodimethylsilyl)phenyl groups on the germanium and tin atoms. The molecular structures of 2 and 3 were determined by X-ray crystallographic analysis, which reveals the structural features of the functionalized four-and five-membered cyclic linkages of the heavior group 14 elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…We have recently reported that the reaction of [o-(fluorodimethylsilyl)phenyl]lithium (1) as an a,g-ambiphilic species III (n = 1) with GeCl 2 produced benzosilagermacyclobutene 2 having two o-(fluorodimethylsilyl)phenyl groups on the germanium atom in the four-membered ring. 5 Compound 2 is expected to exhibit unique reactivity because of the highly strained four-membered ring and the highly electrophilic fluorosilyl functionality. Here we report that the reaction of 2 with KF leads to a ring-opening reaction to give a novel triarylgermyl anion 3 (a,d-ambiphilic species III (n = 2)), in which a germyl anion center and three electrophilic fluorosilyl groups are linked to each other through o-phenylene frameworks, and also that the reaction of 3 with a Lewis acid reversibly leads to a ring-closing reaction to regenerate 2.…”
mentioning
confidence: 99%
“…We have recently reported that the reaction of [o-(fluorodimethylsilyl)phenyl]lithium (1) as an a,g-ambiphilic species III (n = 1) with GeCl 2 produced benzosilagermacyclobutene 2 having two o-(fluorodimethylsilyl)phenyl groups on the germanium atom in the four-membered ring. 5 Compound 2 is expected to exhibit unique reactivity because of the highly strained four-membered ring and the highly electrophilic fluorosilyl functionality. Here we report that the reaction of 2 with KF leads to a ring-opening reaction to give a novel triarylgermyl anion 3 (a,d-ambiphilic species III (n = 2)), in which a germyl anion center and three electrophilic fluorosilyl groups are linked to each other through o-phenylene frameworks, and also that the reaction of 3 with a Lewis acid reversibly leads to a ring-closing reaction to regenerate 2.…”
mentioning
confidence: 99%